Streaming and Students Self-Esteem: A Qualitative Study on Teachers Correspondence Bias - Chin Sook Fui, Prihadi Kususanto (Journal of Educational, Health and Community Psychology, 2012)
This study was aimed to investigate the effect of students streaming practice in Malaysian secondary on students self-esteem through teachers expectancy. 17 teachers and 20 students from art and science streams of secondary schools in Penang, Malaysia were participated in this study. Unstructured interviews were used on teachers to collect the qualitative data of teachers expectancy. The participating students were from the fourth year of secondary school in Malaysian school system (between 16-17 years old, 10 from science stream and 10 from arts stream) were interviewed in order to collect the qualitative data of teachers perceived behavior and self-esteem. Result of this study shown that teachers expected science stream students to have good academic performance but expected arts stream students to be involved in disciplinary problems. Furthermore, science stream students perceived that their teachers were academically supportive but arts stream students perceived that their teachers were focusing on controlling their behavior. On the other hand, findings of this study also revealed that science stream students possed higher level of self-esteem than arts stream students. Accordingly, it was indicated that teachers perceived behavior and teachers expectancy are correlated to one another, and teachers perceived behavior predicts students self-esteem. It was discovered that teachers expected science stream students to be eager to improve their academic performance, and students from arts stream class were likely to be involved in disciplinary problems. Students were found to be aware of their teachers expectancy, and their perception of teachers expectancy affected their self-esteem. While self-esteem was referred to a discrepancy between a students ideal-self and actual-self, it was discovered that both groups of students pictured their ideal-self differently to each other. Science stream students pictured their ideal-selves as a character with overall success, while arts stream students pictured their ideal-selves as a socially well-functioned character. Nevertheless, arts stream students found to have lower self-esteem. It was concluded that streaming affected the students self-esteem through teachers expectancy and perceived behavior.